Precision aerial delivery systems : modeling, dynamics, and control - Yakimenko, Oleg A. (American Institute of Aeronautics and Astronautics, Inc., 2015)
This book provides an overview of the recent developments in precision aerial cargo delivery from the standpoint of developing guidance, navigation and control (GNC) algorithms for the self-guided parafoil and parachute-based aerial delivery systems (PADS). Topics include: PADS and measures of their effectiveness; basic analysis of the ram-air parachute; key factors affecting PADS landing accuracy; aerodynamic characterization of parafoils; equations of motion; stability and steady-state performance; guidance, navigation, and control; glide-angle control; control of nongliding parachute systems; flight test instrumentation; parametrical identification of PADS. -- Edited summary from book.
Keywords: Airdrop.; Delivery of goods.; Gliders (Aeronautics) -- Technological innovations.; Parachutes -- Technological innovations.; elektronické knihy; electronic books